Gastrintestinal Manifestation and Alcoholic - Al Obeidy, Aswad (Journal of the Faculty of Medicine Baghdad, 2005)
Background: Alcohol remains the single most significant Cause of liver disease throughout the Western World, responsible for between 40 and 80% of cases of cirrhosis in different countries. Many of the factors underlying the development of alcoholic liver injwy remain unknown, and significant questions remain about the value of even very basic therapeutic strategies. Patients and Methods: A total number of 113 patients with ALD attending the Gastroenterology and Hepatology teaching hospital between December 2001 and December 2003 were studied for the gastrointestinal, esophagogastroduodenoscopic manifestation of alcoholic liver disease. Results.’The most common presenting symptom was jaundice (62.8%), anorexia, weight loss (39.8-54%) followed by hematemesis and malena (46.9%) and encephalopathy (40.7%). The pattern of the bowel motion was predominantly diarrhea (47.8%>), constipation (16.8%). The most common physical finding was hepatomegaly in (70.8%) followed by jaundice and ascites. The most common EGD jinding was esophageal varieses in (77%>), PHT gastropathy (52%), hemorrhagic gastritis (10.6%), GERD and lax cardia (8.8-15%) and esophageal candidiasis (4.4%). Conclusion: In Iraqi patients with ALD, the most common clinical manifestations were jaundice and hepatomegaly. The pattern of the bowel motion was predominantly diarrhea. The most common EGD finding was esophageal varieses, hemorrhagic gastritis was prevalent and esophageal candidiasis may be a manifestation.